Locally advanced pancreatic cancer: work-up, staging, and local intervention strategies - Veldhuisen, Eran van; Hackert, Thilo (Cancers, 2019)
Locally advanced pancreatic cancer (LAPC) has several definitions but essentially is a nonmetastasized pancreatic cancer, in which upfront resection is considered not beneficial due to extensive vascular involvement and consequent high chance of a nonradical resection. The introduction of FOLFIRINOX chemotherapy and gemcitabine-nab-paclitaxel (gem-nab) has had major implications for the management and outcome of patients with LAPC. After 4–6 months induction chemotherapy, the majority of patients have stable disease or even tumor-regression. Of these, 12 to 35% are successfully downstaged to resectable disease. Several studies have reported a 30–35 months overall survival after resection; although it currently remains unclear if this is a result of the resection or the good response to chemotherapy. Following chemotherapy, selection of patients for resection is difficult, as contrast-enhanced computed-tomography (CT) scan is unreliable in differentiating between viable tumor and fibrosis. In case a resection is not considered possible but stable disease is observed, local ablative techniques are being studied, such as irreversible electroporation, radiofrequency ablation, and stereotactic body radiation therapy. Pragmatic, multicenter, randomized studies will ultimately have to confirm the exact role of both surgical exploration and ablation in these patients. Since evidence-based guidelines for the management of LAPC are lacking, this review proposes a standardized approach for the treatment of LAPC based on the best available evidence.
Gesehen am 04.11.2019